STUDI LITERATUR SISTEMATIS: HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP FINANCIAL PERFORMANCE - Putri, Anggia Marshanda; Putra, Edo Arta Fandala; Fuadah, Luk Luk (Jurnal Riset Terapan Akuntansi, 2025)
Corporate Social Responsibility (CSR) is increasingly viewed as a crucial part of business strategy, not only supporting corporate sustainability but also potentially improving financial performance (FP). However, previous research has shown mixed results, ranging from positive to negative to insignificant. This study aims to systematically review the relationship between CSR and FP across various industry contexts and methodological approaches. The method used was a Systematic Literature Review (SLR) based on the PRISMA guidelines. Data was collected from 45 international (Scopus Q1–Q3) and national (Sinta S1–S3) journal articles relevant to the research topic. The analysis shows that CSR can provide benefits in the form of improved reputation, operational efficiency, stakeholder trust, and strengthened brand value. However, CSR can also be a cost burden if implemented symbolically or not integrated with business strategy. Therefore, the main conclusion of this study is that CSR has the potential to positively impact FP if designed strategically, relevant to stakeholder needs, and implemented within a long-term sustainability framework. This research's contribution lies in presenting a comprehensive mapping of CSR and FP research findings, clarifying inconsistencies in previous findings, and offering new perspectives for academics developing theory and practitioners designing CSR strategies aligned with corporate financial objectives. Keywords: Corporate Social Responsibility, Financial Performance, Systematic Literature Review, PRISMA, Stakeholder Theory